Criminal Law Enforcement Against Land Grabbers in the Jambi Regional Police Jurisdiction - Muhamad Mujib; Achmad Arifulloh (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Based on the provisions of the 1945 Constitution, Law Number 5 of 1960 concerning Basic Agrarian Regulations was drafted. One of the objectives of the Basic Agrarian Law (UUPA) is to provide legal certainty regarding land rights held by the community. An individual or legal entity wishing to have their land ownership officially recognized by the state and their rights guaranteed must register the land to obtain written proof, in the form of a land certificate. A land certificate can be obtained through land registration. Land registration can help determine the status, ownership, rights, area, and use of the land. According to Santoso, proof of land rights is indicated by the existence of a certificate. In reality, the land registration process is still far from perfect. In Indonesia, only about 44 million plots of land have been registered out of approximately 125 million plots of land, calculated from the emergence of the UUPA until 2016. Then in 2017, the Complete Systematic Land Registration Program (PTSL) was formed by the Ministry of ATR/BPN with a target of certifying 126 million plots of land by 2025 in Indonesia. Land certificates serve as a guarantee of legal certainty, as long as no other party can deny it. In general, besides certificates, there are other formal documents that function as documents of land ownership rights, namely ownership deeds. In the negative land registration system, the formal document is referred to as a "deed" of ownership, while in the positive land registration system, the formal document is referred to as a "certificate" of rights. The purpose of land owners in registering land is to obtain a land certificate, so the general public only knows the term certificate in terms of land registration. Meanwhile, the term "deed" refers to an authentic deed prepared by a Land Deed Official (PPAT) and a notary, whose function is to mark land transfers such as inheritance deeds, waqf pledges, sales and purchases, and so on. In Indonesia, cases of land grabbing have long been commonplace, even dating back to the colonial era. The word "encroachment" can mean occupying land or buildings owned by another person without regard to legal regulations. In Latin, this offense is called stellionat, which means embezzlement of rights over immovable objects. In this case, what is meant is land, houses, rice fields, buildings, and so on.